Research trend about counseling based on local wisdom: a bibliometric analysis - Afriyati, Vira; Herawati, Anna Ayu; Pasmawati, Hermi; Rahayu, Puteri Rezki (Education and Social Sciences Review, 2024)
As the counseling field continues to develop, there is increasing recognition of the importance of integrating indigenous knowledge and cultural perspectives into therapeutic practice. The rapid emergence of the field of cultural-based counseling in the last few decades raises critical questions, as to what extent cultural counseling is used in the world of the 21st century. This article aims to provide a detailed overview of using a bibliometric approach to study research trends in counseling based on local wisdom. The method used is bibliometric analysis. The VOS viewer device is an analysis tool with the main data source coming from Scopus articles. Research findings show that the growth in the number of scientific publications related to Local Wisdom-Based Counseling in the 2018-2023 period experienced an increase in interest and focus, namely in 2019 and 2022. Based on the affiliation for the keyword Counseling Based on Local Wisdom, 15 affiliates have publications about Counseling Based on Local Wisdom. In the 2018-2023 period, 9 countries have publications on Counseling Based on Local Wisdom. Furthermore, for the concept that dominates around Local Wisdom-Based Counseling, the highest percentage is in the field of social science, namely 31.3%, while in the fields of psychology and counseling and mental health, it only reaches 12.5%, the remainder is in other fields. The findings in mapping local wisdom-based counseling articles with main data from the Scopus journal are still minimal when compared to the diversity of cultures in the world..